2023
DOI: 10.3390/pathogens12101239
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA Signature in Milk Small Extracellular Vesicles from Cattle Infected with Bovine Leukemia Virus

Md. Matiur Rahman,
Hinata Ishikawa,
Marika Yamauchi
et al.

Abstract: This study aimed to characterize the mRNA signature of milk small extracellular vesicles (sEVs) from BLV-infected cattle. A total of 23 mRNAs, which showed greater abundance in milk sEVs from BLV-infected cattle compared to those from BLV-uninfected (control) cattle, were identified through microarray analyses conducted in our previous study. To assess the significance of these differences in mRNA abundance, milk was collected from six control cattle and twenty-six cattle infected with BLV. The infected cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Matiur Rahman et al in a more recent study, assessed the expression of mRNAs in miEVs from BLV-infected cattle (with high or low proviral load) and uninfected cattle. 155 They found that compared to cattle with a high proviral load of BLV infection, there was a higher expression of CALB1 and TMEM156 in miEVs from cattle with a low proviral load of BLV infection. This finding further supports previous studies that showed the mRNA profile of miEVs can provide a promising resource to reflect the progression of BLV infection.…”
Section: Intestinal Healthmentioning
confidence: 97%
See 1 more Smart Citation
“…Matiur Rahman et al in a more recent study, assessed the expression of mRNAs in miEVs from BLV-infected cattle (with high or low proviral load) and uninfected cattle. 155 They found that compared to cattle with a high proviral load of BLV infection, there was a higher expression of CALB1 and TMEM156 in miEVs from cattle with a low proviral load of BLV infection. This finding further supports previous studies that showed the mRNA profile of miEVs can provide a promising resource to reflect the progression of BLV infection.…”
Section: Intestinal Healthmentioning
confidence: 97%
“…Their study revealed that eight mRNAs ( TMEM156 , SRGN , CXCL8 , DEFB4A , FABP5 , LAPTM5 , LGALS1 , and VIM ) may be potential EBL biomarkers because their expression was remarkably higher in miEVs from infected cattle. Matiur Rahman et al in a more recent study, assessed the expression of mRNAs in miEVs from BLV-infected cattle (with high or low proviral load) and uninfected cattle . They found that compared to cattle with a high proviral load of BLV infection, there was a higher expression of CALB1 and TMEM156 in miEVs from cattle with a low proviral load of BLV infection.…”
Section: Biomedical Applications Of Mievsmentioning
confidence: 99%